1974
DOI: 10.1111/j.1469-8137.1974.tb01322.x
|View full text |Cite
|
Sign up to set email alerts
|

The Three‐dimensional Shape of Plant Cells and Its Relationship to Pattern of Tissue Growth

Abstract: SUMMARYTwo geometric models were devised for the shape of plant cells, one for those cells undergoing three-dimensional expansion and the other for cells enlarging in one dimension (elongation). Probability distributions for the number and shape of wall facets were generated from the models and compared favourably with those found for real cells by other investigators. The i-D growth model gave averages for the facet number and geometry of cells at interphase, division and daughter cell formation that closely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

1976
1976
2019
2019

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…It would also seem that the sinuous growth pattern would provide more secure attachment between epidermal and mesophyll cells. The number of palisade cells in contact with an epidermal cell varies from one to nine and averages four (Korn, 1974a) but some of these contacts involve small areas. By regional expansion of the basal periclinal walls in accommodation to lobe growth more contact space with mesophyll cells is possible than by uniform growth alone and, also, a more uniform spacing between mesophyll cells becomes possible (Figs.…”
Section: Abnormal Gametophytes ' ' •' ^'mentioning
confidence: 99%
See 2 more Smart Citations
“…It would also seem that the sinuous growth pattern would provide more secure attachment between epidermal and mesophyll cells. The number of palisade cells in contact with an epidermal cell varies from one to nine and averages four (Korn, 1974a) but some of these contacts involve small areas. By regional expansion of the basal periclinal walls in accommodation to lobe growth more contact space with mesophyll cells is possible than by uniform growth alone and, also, a more uniform spacing between mesophyll cells becomes possible (Figs.…”
Section: Abnormal Gametophytes ' ' •' ^'mentioning
confidence: 99%
“…Cultures of gametophytes of Dryopteris thelypteris were used for growth studies (Korn, 1974a) within which a low frequency (io~^) of atypical plants were found. These thalli are characterized by the replacement of the single apical cell by an elongated group of cells usually containing some xylem cells (Plate i, Nos.…”
Section: Abnormal Gametophytes ' ' •' ^'mentioning
confidence: 99%
See 1 more Smart Citation
“…A vertex can open to form an air space, can deposit additional wall material and also prevent new cell plates from becoming attached (Sinnott and Bloch, 1941;Korn, 1974). Also, in considering an edge as a morphogenetic region it becomes possible to understand how one may influence another through some spreading effect along its surface, much in the same manner as wall thickenings extend over increasingly greater areas during collenehyma maturation.…”
Section: Model Constructionmentioning
confidence: 99%
“…Although Barratt (1916) carefully followed the history of cell patterns in the relationship to the locations of air spaces, she did not identify the important ordering process(es) which determine the initial arrangement of air spaces. This study is an attempt to characterize this ordering feature through model construction that simulates several statistical, and therefore quantitative, features of the adult tissue in a manner carried out previously on other tissues (Korn, 1972(Korn, , 1974Korn and Spalding, 1973;Korn and Fredrick, 1973). v.'-5ri.fi iHciU''.…”
mentioning
confidence: 99%